Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/biology12070992
|View full text |Cite
|
Sign up to set email alerts
|

Clodronate Liposome-Mediated Phagocytic Hemocyte Depletion Affects the Regeneration of the Cephalic Tentacle of the Invasive Snail, Pomacea canaliculata

Abstract: After amputation, granular hemocytes infiltrate the blastema of regenerating cephalic tentacles of the freshwater snail Pomacea canaliculata. Here, the circulating phagocytic hemocytes were chemically depleted by injecting the snails with clodronate liposomes, and the effects on the cephalic tentacle regeneration onset and on Pc-Hemocyanin, Pc-transglutaminase (Pc-TG) and Pc-Allograft Inflammatory Factor-1 (Pc-AIF-1) gene expressions were investigated. Flow cytometry analysis demonstrated that clodronate lipos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Müller glia cells have been shown to be necessary for retinal cells regeneration in zebrafish. In apple snails, it has been previously observed that clodronate treatment depletes circulating phagocytic hemocytes and delays the formation of the blastema after the amputation of the cephalic tentacle 40 . This suggests that the roles of the immune and nervous systems in P. canaliculata eye regeneration need to be further investigated.…”
Section: Regeneration Of Missing Body Parts and Specifically Eyesmentioning
confidence: 99%
“…Müller glia cells have been shown to be necessary for retinal cells regeneration in zebrafish. In apple snails, it has been previously observed that clodronate treatment depletes circulating phagocytic hemocytes and delays the formation of the blastema after the amputation of the cephalic tentacle 40 . This suggests that the roles of the immune and nervous systems in P. canaliculata eye regeneration need to be further investigated.…”
Section: Regeneration Of Missing Body Parts and Specifically Eyesmentioning
confidence: 99%